Large bowel obstruction in palliative care: overview, management and monitoring - Rahimuddin, Noora O.; Al-Fodari, Fatma A.; Yatimi, Laila M.; Alsaffar, Ahmed M.; Kadir, Basmah K.; Alrazhi, Tariq H.; Alzaylaee, Waleed A.; Almarri, Mohammad S.; Alshelahi, Sameer S.; Almuhaiteeb, Mohammad A.; Alhamad, Hamad A. (International Journal Of Community Medicine And Public Health, 2021)
Patients with pelvic and abdominal cancers usually present with bowel obstruction, especially peritoneal, colorectal, and pancreatic carcinomatosis. A poor prognosis has been reported for patients that suffer from gastrointestinal bowel obstruction secondary to later stage carcinomatosis, although maximal treatment approaches might have been administered. In this context, these patients are suggested to survive for only a few weeks to months, and parenteral nutrition did not enhance the outcomes in these situations. Medical treatment includes the administration of corticosteroids, opioids, anticholinergics, octreotide, and anti-emetics, while surgical outcomes might be more efficacious with more favorable clinical outcomes. However, these operations have been reported with multiple complications that might worsen the prognosis. Stent application is another non-surgical modality with fewer adverse events. Nevertheless, evidence regarding its superiority over the surgical approaches is conflicting among the different studies in the literature. Accordingly, further investigations are still needed for adequate validation.